A spatial multi-criteria evaluation for site selection of offshore marine fish farm in the Ligurian Sea, Italy - Dapueto, G; Massa, F; Costa, S; Cimoli, L; Olivari, E; Chiantore, M; Federici, B; Povero, P (Elsevier, 2015)
Mariculture is a relatively new activity that is expanding globally and interacts with other coastal uses. Therefore, it is necessary to allocate suitable sites from environmental, economic and social points of view, involving different stakeholders in the decision-making process. In particular, in the Ligurian Sea (Italy), for its environmental characteristics and tradition, fish farming should be further boosted and an accurate marine spatial planning should be done. This paper presents a spatial multi-criteria evaluation (SMCE) addressed to identify suitable areas for siting offshore medium size fish farms in the Ligurian Sea at the regional scale. The SMCE procedure follows an integrated approach that can be potentially adapted and applied to any coastal system. The site selection is based on the definition of criteria that assess their suitability and on conditions related to the entire study area. Suitability values are ranked on a scale from 1 (suitable) to 10 (optimal). More than 9000ha were identified and almost 40% of this area gets high suitability values, from 7 to 9, pointing out the untapped potential for Ligurian marine coastal zone. Results demonstrate that our SMCE, and in particular its procedure, allows identifying the most suitable areas in an easy and quick way and solving effectively the complex spatial problem of suitable site selection for fish farming.